Domestic cycles, financial cycles, and policies: What has gone wrong? - Daniel Daianu (Center for Social and Economic Research (CASE), 2017)
The financial crisis and its ensuing effects have brought back into the limelight the issue of cycles and of policies which fuel or mitigate crises. Cognitive and operational models in economics and business are questioned. There is a specter of much lower economic growth in the industrialized world. Central banks are over-burdened. This makes central bankers' lives much more complicated and obfuscates the boundaries between monetary policy and fiscal policy, especially when financial stability gets to center stage. New systemic risks show up in capital markets. The eurozone has escaped collapse owing to the European Central Bank's extraordinary operations and large macro-imbalance corrections in its periphery, but major threats persist. This paper focuses on economic cycles and policies in an international (European) context. Attention is paid to linkages between domestic cycles and the European financial cycle, drivers of financial cycles, finance deregulation and systemic risks, ultra-low interest rates, the international policy regime, and global stability. The experience of European emerging economies is taken into account.
Keywords: E31; E32; E44; E51; E62; F21; F34; F44; F62; 330; financial crisis; financial cycle; secular stagnation; debt overhang; low interest rates; policy rates; fiscal policy; monetary policy; emerging economies; Konjunktur; Konjunkturzusammenhang; Finanzkrise; Geldpolitik; Öffentliche Schulden; Finanzmarktregulierung; EU-Staaten